Predictors of Survival Among Preterm Neonates Admitted to Felege Hiwot Comprehensive Specialized Hospital, Northwest Ethiopia - Belay, Demeke Mesfin; Worku, Workie Zemene; Wondim, Amare; Hailemeskel, Habtamu Shimels; Bayih, Wubet Alebachew (Frontiers in Pediatrics, 2022)
Abstract Background: Prematurity is the primary cause of neonatal mortality in the world. In previous study, even though prematurity was the leading cause of neonatal mortality, the survival rate and its predictors may be varied from setting to setting and time to time due to different reasons. Therefore, this study aimed to assess the survival probability and predictors of mortality among preterm neonates at Felege Hiwot comprehensive specialized hospital. Methods: This is a retrospective follow up study included 542 randomly selected preterm neonates admitted at Felege Hiwot comprehensive specialized hospital from period of 2016-2020. Semi-parametric and parametric survival models were fitted to identify the survival probability of preterm neonates and its association with different predictors. The best fit model was selected using Akaike’s information criteria, Bayesian information criteria and likelihood rate criteria. Results: The cumulative incidence and incidence rate of mortality among preterm neonates were 31 per 100 live births and 3.5 per 100 neonate days, respectively. From the adjusted cox-proportional-hazard model, predictors with higher preterm mortality risk include the presence of neonatal respiratory distress syndrome [AHR=2.55, 95% CI: 1.23; 3.74], perinatal asphyxia [AHR=4.26, 95% CI: 1.35; 6.79] and jaundice [AHR=3.25, 95% CI: 2.14, 7.24]. However, admission weight of 1500g–2499g (AHR=0.23, 95% CI: 0.11, 0.56) and ≥2500g (AHR=0.12, 95% CI: 0.02; 0.32), early breastfeeding [AHR=0.44, 95% CI: 0.36; 0.48] and kangaroo mother care [AHR = 0.11, 95% CI: 0 .03; 0.15] were protective predictors of preterm mortality. Conclusion: The cumulative incidence of mortality among preterm neonates was higher than the national incidence of preterm mortality (29.31%). Cox-proportional hazard model was the best fit model to identify the predictors of survival among preterm neonates. Thus, predictors such as, low birth weight, respiratory distress syndrome, perinatal asphyxia and jaundice are manageable. Therefore, considerable attentions such as, intensive phototherapy, optimal calorie feeding, oxygenation and good thermal care should be given for admitted preterm neonates. Keywords: Ethiopia, neonates, Predictors, Preterm, Survival